Organizaciones comunitarias de prestación del servicio del agua en Villavicencio (Colombia): repercusiones, desafíos y propuestas para el abastecimiento de agua en las ciudades - Natalia Duarte Cáceres (2022)
This research analyzes community water supply organizations, their effects (symbolic, political and technical), as well as possibilities of articulation and complementarity with public management. For this purpose, three community water service organizations were selected in the city of Villavicencio, Colombia. Located where the eastern mountain range of the Colombian Andes meets the region known as Llanos Orientales, in the center of the country, Villavicencio has 531,275 inhabitants and has undergone strong urban and socioeconomic transformations in the last twenty years. The main provider of water supply services in the city is the Empresa de Acueducto y Alcantarillado de Villavicencio (EAAV), a public company that has been criticized for various technical and administrative deficiencies, such as extended service cuts. In this context, a multiplicity of private and community providers have emerged in the urban area, challenging the idea that the universal and industrial water distribution model is a natural monopoly and the only - and ideal - way for water supply in the cities. Through an action research methodology, this work, carried out between 2017 and 2022, employed various qualitative methodological procedures such as participant observation, semi-structured interviews, community censuses and participatory workshops. Guided by the political ecology approach, the "commons" perspective of the Theory of Collective Action (Ostrom, 2011), and Dardot and Laval's (2010, 2015) arguments about "the common" as a political process, this research raises three main considerations. First, it questions the technical relevance and social effects of the "big system" of water infrastructure networks. Second, although community water organizations also present conflicts and difficulties, they can be recognized as a flexible and more democratic supply model, where community organizations have also given rise to broader social movements that question the principles - normative and ideological - that underpin the water services management in Colombia. Third, and as a general proposal of this research, it suggests the possibility of articulating public action with community water supply strategies at a local scale, forging new paradigms of water service management that are more democratic, more sustainable and more relevant to the reality of the cities.